The effects of tantalum addition on the microtexture and mechanical behaviour of tungsten for ITER applications - Tejado, Elena (2016)
Tungsten (W) and its alloys are very promising materials for producing plasma-facing components (PFCs) in the fusion power reactors of the near future, even as a structural part in them. However, whereas the properties of pure tungsten are suitable for a PFC, its structural applications are still limited due to its low toughness, ductile to brittle transition temperature and recrystallization behaviour. Therefore, many efforts have been made to improve its performance by alloying tungsten with other elements. Hence, in this investigation, the thermo-mechanical performance of two new tungsten-tantalum materials has been evaluated. Materials with W–5wt.%Ta and W–15wt.%Ta were processed by mechanical alloying (MA) and later consolidation by hot isostatic pressing (HIP), with distinct settings for each composition. Thus, it was possible to determine the relationship between the microstructure and the addition of Ta with the macroscopic mechanical properties. These were measured by means of hardness, flexural strength and fracture toughness, in the temperature range of 300–1473 K. The microstructure and the fracture surfaces features of the tested materials were analysed by Field Emission Scanning Electron Microscopy (FESEM).